Back Cover: Nonmonotonic Hydration Behavior of Bovine Serum Albumin in Alcohol/Water Binary Mixtures: A Terahertz Spectroscopic Investigation (ChemPhysChem 7/2017). Issue 7 (5th April 2017) - Das, Dipak Kumar; Das Mahanta, Debasish; Mitra, Rajib Kumar
Abstract : The Back Cover picture summarizes the change in the collective hydration dynamics of a protein in water–alcohol binary mixtures. More information can be found in the Full Paper by D. K. Das et al. onpage 749 in Issue 7, 2017 (DOI:10.1002/cphc.201601217 ).